2002
DOI: 10.1074/jbc.m206804200
|View full text |Cite
|
Sign up to set email alerts
|

pH-induced Collapse of the Extracellular Loops ClosesEscherichia coli Maltoporin and Allows the Study of Asymmetric Sugar Binding

Abstract: LamB (maltoporin) is essential for the uptake of maltose and malto-oligosaccharides across the outer membrane of Escherichia coli. Purified LamB was reconstituted in artificial lipid bilayer membranes forming channels in the permanently open configuration at neutral pH. Almost complete channel closure was observed when the pH on both sides of the membrane was lowered to pH 4. When LamB was added to only one side of the membrane, the cis-side, and the pH was lowered at either side of the membrane, the cis-or th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
27
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 35 publications
5
27
0
Order By: Relevance
“…In agreement with the orientation of maltoporin channels suggested by the kinetics of maltohexaose transport through the mutants W74A and F227A, we conclude that maltoporin inserts with the periplasmic turns leaving the extracellular loops oriented at the cis-side of the membrane (Fig. 8), confirming the proposal of Benz and co-workers (21,22). It is noteworthy that Van Gelder et al (23) found an opposite orientation of maltoporin in lipid bilayers.…”
Section: Fig 7 Current Fluctuations Spectral Densities In Maltohexasupporting
confidence: 79%
See 1 more Smart Citation
“…In agreement with the orientation of maltoporin channels suggested by the kinetics of maltohexaose transport through the mutants W74A and F227A, we conclude that maltoporin inserts with the periplasmic turns leaving the extracellular loops oriented at the cis-side of the membrane (Fig. 8), confirming the proposal of Benz and co-workers (21,22). It is noteworthy that Van Gelder et al (23) found an opposite orientation of maltoporin in lipid bilayers.…”
Section: Fig 7 Current Fluctuations Spectral Densities In Maltohexasupporting
confidence: 79%
“…Based on the binding asymmetry of a pseudooligosaccharide modified at its nonreducing end (20), on mutants deleted in the large extracellular loops, and on asymmetrical pH-induced closure of the channel proteins, Benz and co-workers (21,22) propose that maltoporin preferentially inserts with the short periplasmic turns moving through the membrane. In contrast, Van Gelder et al (23) used bacteriophage-and observed the opposite orientation.…”
mentioning
confidence: 99%
“…In principle, this could be due to either a switch of MspA to a closed channel conformation or to a reduced reconstitution efficiency. Voltage-and pH-dependent conformational changes of extracellular loops leading to channel closure were demonstrated for the general porin OmpF (47) and for the maltose-specific porin LamB (48). Since substantial extracellular domains were observed in electron microscopy pictures of MspA in the cell wall of M. smegmatis (12), it seems more likely that the urea-or SDS-induced loss of channel activity reflects structural alterations of MspA rather than a reduced reconstitution efficiency of MspA in lipid bilayer experiments.…”
Section: Figmentioning
confidence: 95%
“…Membranes were formed either from a 1% solution of diphytanoyl phosphatidylcholine (Avanti Polar Lipids, Alabaster, AL) or from a 1% solution of a mixture of diphytanoyl phosphatidylcholine and cholesterol (molar ratio 1:1) or from a 1% solution of oxidized cholesterol (36) in n-decane. Reduction of pH was achieved by the addition of predetermined amounts of 0.1% HCl to the volume on one or both sides bathing lipid bilayer membranes (37).…”
mentioning
confidence: 99%